Benefits of a Voluntary Cell Phone Abstinence Intervention in General Psychology Courses. (October 2019) - Whittington, Brandon L.
Although cell phones are often discussed as a problem in higher education research, the literature focuses largely on disciplinary tactics or integration of phones into the curriculum. The present study provides further support for the use of positive reinforcement to minimize the negative effects of cell phones in the classroom. A quasi-experimental design randomly assigned course sections of general psychology to participate in an electronic device-free project for the entire semester or only the second half of the semester. Results provide support for previous research of the deleterious effects of cell phone use on exam scores and further expands the literature by also demonstrating negative effects of cell phone use on classmate connection and course satisfaction.